The Waning of Kiai's Role: Transformation from Cultural Broker to Political Broker in Regional Head Election - Muslim Mufti (Khazanah Sosial, 2023)
This study aims to analyze the transformation of the role of Kiai in the local political context, focusing on their role as cultural broker to become political broker in Banten Regional Head Election. This research involved a qualitative study involving in-depth interviews with Kiai in the Banten area and an analysis of related documents. The study's results found a change in the role of the Kiai from being a cultural broker responsible for spreading religious and cultural teachings to the public into a political broker involved in the political process and regional head elections. Kiai not only acts as spiritual leaders but also become determinants in the local political process, including in the regional head elections. Kyai uses their religious influence and authority to influence political preferences and voter behavior. They also have access to political networks and play a role in coordinating political support for certain regional head candidates. This research provides a better understanding of the transformation of Kiai's role from a cultural broker to a political broker in the political process. This study implies that it is a basis for developing a comprehensive understanding of local political dynamics in Indonesia and the role of religion in the political process.